Islahi social capital: a conceptual approach towards faith-based development and poverty alleviation - Malik, Maszlee (Centre for Islamic Area Studies at Kyoto University (KIAS), 2014)

(untitled)
Poverty is amongst the pandemic that is synonym with Muslim countries. Many theories and formulations have been developed to overcome the issue of poverty. Though many attempt to eradicate poverty with different type of models, however, not many of them is interested to inculcate the faith-based elements in their theses. Due to the current trend of social capital as one of the means for development as recognized by many international institutions, an ontological-based epistemological approached is needed in determining on how Islamic values could be incorporated into this latest fad du jour to present a whole new set of Islamic political ijtihad (reasoning). This paper will analytically investigate on how the concept of islah (continuous reform) in Islam could be an essential conceptualized tool within the framework of social capital as another approach for development and poverty eradication. This proposed ontological-based conceptual attempt is to be called as ‘Islahi Social Capital’.